Removal of Cr(VI) from aqueous solution using magnetite/non-oxidative graphene composites: Synergetic effect of Cr(VI) on dyes removal. Issue 18 (11th December 2016) - Zheng, Mengliang; Ahn, Yongtae; Yoon, Yeojoon; Park, Won Kyu; Jung, Youmi; Kwon, Minhwan; Yang, Woo Seok; Kang, Joon-Wun
ABSTRACT: Non-oxidative graphene (nOG) synthesized from natural graphite powder was modified with magnetite (Fe3 O4 ) for removal of Cr(VI) and dyes in aqueous solution. The adsorption behavior of Cr(VI) on Fe3 O4 /nOG (M-nOG) was systematically investigated, and the simultaneous adsorption of Cr(VI) and dyes such as methylene blue (MB) and rhodamine B (RhB) was evaluated. Adsorption kinetic and isotherm of Cr(VI) were fitted well with pseudo-second-order model and Sips model, respectively. For the binary system, Cr(VI) removal was not affected with increasing the dye concentration, whereas the adsorption capacity of both MB and RhB was enhanced with increasing the concentrations of Cr(VI).